Effect of carnitine supplementation on fatigue level in the gastrocnemius muscle of trained and sedentary rats - Rossana Anelice Gomez; Miguel de Arruda; Fabio Pinhero Ramos; Marco Antonio Cossio Bolaños (Universidade Federal de Santa Catarina, 2012)
L-carnitine, considered to be of great value in metabolic processes, plays an important role in the mitochondrial β-oxidation process. It may be used to improve athletic performance and to maintain a higher workload during exercise. This study aimed to investigate the effect of L-carnitine supplementation on muscle fatigue in sciatic nerve-gastrocnemius muscle preparations in sedentary and trained rats. The animals were divided into 4 groups: non-supplemented sedentary (NSS), supplemented sedentary (SS), non-supplemented trained (NST), and supplemented trained (ST) rats. The animals were trained in daily 1-h sessions (5 days/week) and received chronic oral L-carnitine supplementation (1 mg/mL) for 4 weeks. Muscle fatigue was determined by supramaximal tetanic stimulation of the sciatic nerve (50 Hz). Time values for strength reduction were significantly different (p<0.05) between NSS vs. SS and NST vs. ST rats. No significant differences were observed between SS vs. ST and NST vs. NSS rats. These findings demonstrate that L-carnitine lengthen the time required for induction of muscle fatigue.